Human Dignity Conference - Part 1
Recording of an international conference in honor of outgoing Hungarian President Árpád Göncz held at the Hungarian Academy of Sciences in Budapest. The conference, entitled "On Human Dignity," was organized by the Hungarian Academy of Sciences, Central European University and the Faculty of Law and Political Science of Eötvös Loránd University. The opening lecture is delivered by Nigerian writer Wole Soyinka, who was awarded the Nobel Prize for Literature in 1986. Among numerous scholars, researchers and professors, participants include, in the order of their appearance, Romanian philosopher Andrei Pleşu, economist and philanthropist George Soros, Katalin Gönczöl, the past first Parliamentary Commissioner for Human Rights (Ombudsman) of Hungary, Mário Soares, the former President of Portugal, Shlomo Avineri, an Israeli political scientist and Recurring Visiting Professor at CEU, Veena Das, Professor of Anthropology at the Johns Hopkins University and economist János Kornai. This recording contains the moderator’s introductory words about the guests of the conference as well as the Q&A sessions.